Bone volumetric density, geometry, and strength in female and male collegiate runners - Smock, A. J.; Hughes, J. M.; Popp, K. L.; Wetzsteon, R. J.; Stovitz, S. D.; Kaufmann, B. C.; Kurzer, M. S.; Petit, M. A. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To explore differences in tibial bone geometry, volumetric density, and estimates of bone strength in runners and healthy controls.